2015
DOI: 10.13075/ijomeh.1896.00630
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to culturable and total microbiota in cultural heritage conservation laboratories

Abstract: Objectives: To date, the scientific source materials usually focus on microbial contamination of the museum or library collections themselves, while the exposure of persons who professionally deal with this type of objects in cultural heritage conservation laboratories is ignored. Material and Methods: The study was carried out in 9 naturally ventilated conservation laboratories with no history of water damage. Viable (understood as culturable) bioaerosol stationary samples were collected in both outdoor and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…However, these genera occurred commonly in atmospheric air, the presence of them at the workplaces may constitute potential hazards to employees (group 2 according to their level of risk of infection and allergy) [23]. Fungal quality assessment of examined workplaces is similar to results obtained by other researchers [18,[31][32][33]. Pathogenic A. fumigatus was found in swab samples from an office keyboard and an ambulance ventilation system.…”
Section: Discussionsupporting
confidence: 52%
“…However, these genera occurred commonly in atmospheric air, the presence of them at the workplaces may constitute potential hazards to employees (group 2 according to their level of risk of infection and allergy) [23]. Fungal quality assessment of examined workplaces is similar to results obtained by other researchers [18,[31][32][33]. Pathogenic A. fumigatus was found in swab samples from an office keyboard and an ambulance ventilation system.…”
Section: Discussionsupporting
confidence: 52%
“…Sampling the total air concentration of particulate matter only allows a simple estimate of exposure or indoor contamination that may not correlate with observed health effects [57]. The present study obtained data related with two aerodynamic diameters, allowing a more detailed risk assessment for patients and workers.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Qian et al (2012) observed that the concentrations of microbial particle mass in an occupied classroom of a university were about ten times higher than those observed in the outdoor air. A number of proposed hygienic standards suggest using the ratio of microbial concentrations measured inside and outside studied facilities in order to determine the admissible contamination (Górny et al 2016). According to Burge (1990), if the concentration of bioaerosol indoors exceeds 1.0 9 10 3 CFU/m 3 and persistently exceeds at least twofold the concentration found outdoors, it is necessary to take preventive measures in terms of the indoor air quality.…”
Section: Resultsmentioning
confidence: 99%